Hydrogels in Cardiac Surgery: Versatile Platforms for Tissue Repair, Adhesion Prevention, and Localized Therapeutics - Seok Beom Hong; Jin-Oh Jeong; Hoon Choi (Gels)
Hydrogels have emerged as multifunctional biomaterials in cardiac surgery, offering promising solutions for myocardial regeneration, adhesion prevention, valve engineering, and localized drug and gene delivery. Their high water content, biocompatibility, and mechanical tunability enable close emulation of the cardiac extracellular matrix, supporting cellular viability and integration under dynamic physiological conditions. In myocardial repair, injectable and patch-forming hydrogels have been shown to be effective in reducing infarct size, promoting angiogenesis, and preserving contractile function. Hydrogel coatings and films have been designed as adhesion barriers to minimize pericardial adhesions after cardiotomy and improve reoperative safety. In heart valve and patch engineering, hydrogels contribute to scaffold design by providing bio-instructive, mechanically resilient, and printable matrices that are compatible with 3D fabrication. Furthermore, hydrogels serve as localized delivery platforms for small molecules, proteins, and nucleic acids, enabling sustained or stimuli-responsive release while minimizing systemic toxicity. Despite these advances, challenges such as mechanical durability, immune compatibility, and translational scalability persist. Ongoing innovations in smart polymer chemistry, hybrid composite design, and patient-specific manufacturing are addressing these limitations. This review aims to provide an integrated perspective on the application of hydrogels in cardiac surgery. The relevant literature was identified through a narrative search of PubMed, Scopus, Web of Science, Embase, and Google Scholar. Taken together, hydrogels offer a uniquely versatile and clinically translatable platform for addressing the multifaceted challenges of cardiac surgery. Hydrogels are poised to redefine clinical strategies in cardiac surgery by enabling tailored, bioresponsive, and functionally integrated therapies.